1984
DOI: 10.7164/antibiotics.37.253
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of chitin metabolism by avermectin in susceptible organisms.

Abstract: Avermectin inhibits Mucor miehei and Artemia salina chitin synthesis and to a degree DNA synthesis in the former. The antibiotic interferes with chitin turnover in brine shrimp and inhibits Streptomyces antibioticus chitinase activity in vitro. In light of the proposed mode of action of avermectin and the anomolies in the literature, it is proposed that avermectin can kill susceptible organisms not only by a neurotoxic mechanism but also by inhibiting chitin turnover and synthesis at low concentration and thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Thus, it was surprising that we did not detect larger impacts on the more abundant members of the microbial community. Changes to the fungal community might have been expected, given that albendazole has antifungal activities, and avermectins have been shown to inhibit chitin synthesis 7 . However, anaerobic fungi occupy a specialised niche in the gut, and their physiology differs considerably to that of aerobic fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was surprising that we did not detect larger impacts on the more abundant members of the microbial community. Changes to the fungal community might have been expected, given that albendazole has antifungal activities, and avermectins have been shown to inhibit chitin synthesis 7 . However, anaerobic fungi occupy a specialised niche in the gut, and their physiology differs considerably to that of aerobic fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…This study shows firstly that the decrease of epidermal penetration of AVM is related to the upregulation of DmeCHS1/2 in AVM-resistant Drosophila larvae compared with that in the susceptible larvae. However, an earlier study showed that AVMs can inhibit chitin synthesis in Mucor miehei and Artemia salina [ 40 ]. The difference may be due to the different doses of AVM used in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…This effect can be induced at neuromuscular junctions (Wang & Pong, 1982;Campbell, 1985) and within the central nervous system (Lummis & Sattelle, 1985). Any effect upon chitin synthesis (Calcott & Fatig, 1984) has yet to be demonstrated in insects. Any effect upon chitin synthesis (Calcott & Fatig, 1984) has yet to be demonstrated in insects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been suggested that ivermectin acts directly upon chloride channels independently of GABA both in the central nervous system and at neuromuscular junctions (Tanaka & Matsumura, 1985). Any effect upon chitin synthesis (Calcott & Fatig, 1984) has yet to be demonstrated in insects.…”
Section: Discussionmentioning
confidence: 99%